KILKA UWAG O MODELACH MEDIALNEGO PRZEKAZU MNIEJ POPULARNYCH DYSCYPLIN SPORTOWYCH - Tworek, Artur (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents and critically analyzes selected methods of constructing a press and television commentaries in Polish on less popular sports (luge, alpine skiing, handball).